2015
DOI: 10.3329/jesnr.v8i1.24682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Quality, Environmental Sanitation and Hygiene Practices on Health of School Going Children of Urban Slum Areas

Abstract: The study was carried out among the 246 school going children of urban slum of Tangail district and random sampling methods were applied. Slum population has been increasing in Bangladesh over the last three decades along with the growth and expansion of cities and towns.The facilities in urban slums were very much unsatisfactory due to lack of proper water supply and adequate hygiene and sanitation facilities. The good hygienic and sanitation knowledge and the practice have been found to be significantly low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
1
1
0
1
Order By: Relevance
“…The anthropometric result of study in urban slums of Tangail Pourashava recorded that 28.9% children were stunted and 69.9% were normal and only 1.2% were over normal. 16 This indicates better conditions of school going children compare to our study, which showed 38% of school going children were moderately stunted and 58% were normal. But in dropout group prevalence of stunting was higher (68% moderately stunted, 22% normal and 10% severely stunted) than school going children.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The anthropometric result of study in urban slums of Tangail Pourashava recorded that 28.9% children were stunted and 69.9% were normal and only 1.2% were over normal. 16 This indicates better conditions of school going children compare to our study, which showed 38% of school going children were moderately stunted and 58% were normal. But in dropout group prevalence of stunting was higher (68% moderately stunted, 22% normal and 10% severely stunted) than school going children.…”
Section: Discussionsupporting
confidence: 56%
“…So, environmental sanitation and hygiene practices have a signifi cant impact (P-value ≤ 0.05) on the health of a school going child of the slum. 26…”
Section: Discussionmentioning
confidence: 99%
“…Begitupun sebaliknya bahwa terserang penyakit infeksi mengganggu metabolisme zat-zat gizi di dalam tubuh sehingga pemanfaatan zat gizi di dalam tubuh menjadi tidak optimal dan akan berdampak pertumbuhan. 28,29 Pada penelitian ini, morbiditas ditemukan tidak berhubungan dengan status gizi (p>0,05). Hasil yang sama juga ditemukan oleh Elvandari tahun 2017 dalam penilaian status gizi anak usia 1-3 tahun di Jawa Tengah.…”
Section: Pembahasanunclassified